The Clinical Impact of Quantitative Cell-free DNA, KRAS, and BRAF Mutations on Response to Anti-EGFR Treatment in Patients with Metastatic Colorectal Cancer - Moradi-Marjaneh, Reyhaneh; Asgharzadeh, Fereshteh; Khordad, Elnaz; Marjaneh, Mahdi M. (Current Pharmaceutical Design, 2021)
Colorectal cancer (CRC) is one of the most common leading causes of cancer death in the world. Although EGFR inhibitors have established efficacy in metastatic colorectal cancer (mCRC), some patients do not respond to this treatment. The EGFR inhibitors' failure and acquired resistance are partly due to KRAS and BRAF mutations. Thus, prognostic biomarkers that help to select eligible patients are highly in demand. To improve patient selection, assessment of mutational status in circulating cell free DNA (cfDNA), which possibly represents the dynamicity of tumor genetic status better than tumor tissue, could be advantageous. This review summarizes the current knowledge of the prognostic value of cfDNA in patients with mCRC treated with EGFR inhibitors with emphasis on the clinical importance of identification of KRAS and BRAF mutations.
Keywords: BRAF